Significant liver fibrosis, as assessed by fibroscan, is independently associated with chronic vascular complications of type 2 diabetes: A multicenter study. (July 2021) - Mikolasevic, I.; Rahelic, D.; Turk-Wensween, T.; Ruzic, A.; Domislovic, V.; Hauser, G.; Matic, T.; Radic-Kristo, D.; Krznaric, Z.; Radic, M.; Filipec Kanizaj, T.; Martinovic, M.; et al.
Abstract: Aims: The aim of this study was to investigate whether controlled attenuation parameter (CAP) and liver stiffness measurement (LSM), as assessed by vibration-controlled transient elastography (VCTE), are associated with chronic vascular complications of diabetes mellitus type 2 (T2DM). Methods: We studied 442 outpatients with established T2DM, and who underwent VCTE and extensive assessment of chronic vascular complications of diabetes. Results: A quarter of analyzed patients had a previous history of myocardial infarction and/or ischemic stroke, and about half of them had at least one microvascular complication (chronic kidney disease (CKD), retinopathy or polyneuropathy). The prevalence of liver steatosis (i.e., CAP ≥ 238 dB/m) and significant liver fibrosis (i.e., LSM ≥ 7.0/6.2 kPa) was 84.2% and 46.6%, respectively. Significant liver fibrosis was associated with an increased likelihood of having myocardial infarction (adjusted-odds ratio 6.61, 95%CI 1.66–37.4), peripheral polyneuropathy (adjusted-OR 4.55, 95%CI 1.25–16.6), CKD (adjusted-OR 4.54, 95%CI 1.24–16.6) or retinopathy (adjusted-OR 1.81, 95%CI 1.62–1.97), independently of cardiometabolic risk factors, diabetes-related variables, and other potential confounders. Liver steatosis was not independently associated with any macro-/microvascular diabetic complications. Conclusions: Significant liver fibrosis is strongly associated with the presence of macro-/microvascular complications in patients with T2DM. These results offer a new perspective on the follow-up of people with T2DM.